Dysplasia-Associated Polypoid Mucosal Lesion in a Pelvic Pouch after Restorative Proctocolectomy for Ulcerative Colitis - Hugh Freeman (Canadian Journal of Gastroenterology)
A 32-year-old man with ulcerative colitis had a colectomy for toxic colitis. Later, a rectal mucosectomy was performed along with the creation of a pelvic pouch. In 1998, approximately 10 years after this staged restorative proctocolectomy was completed, endoscopic examination of the pelvic pouch detected a small mucosal polypoid mass lesion. Although the lesion had the macroscopic appearance of an inflammatory polyp, microscopic sections of the resected lesion revealed dysplastic changes. Endoscopic polypectomy was performed to remove the lesion, and further histological surveillance examinations of the pelvic pouch have not detected additional dysplastic mucosal changes.